Outside the Text: Retheorizing Empiricism and Identity - Sanchez, Raul (College English, 2012)
Recent theoretical and technological developments, including concepts of networking elaborated by Bruno Latour, enable composition studies to take an empiricist turn toward issues of identity. More specifically, these developments help the field more strongly connect the figure of the writing-subject to the experiences of actual writers.